UNMASKING SHADOWS: ILLUMINATING BARRIERS AND TRANSFORMATIVE INTERVENTIONS IN HUMAN TRAFFICKING FOR SOCIAL WORK ADVANCEMENT IN ALBANIA. A LITERATURE REVIEW - Lesia Shuranova; Radek Vistořín; Jitka Vacková; Renata Švestková; Radka Prokešová; Klaudie Němečková (Клінічна та профілактична медицина)
Introduction. Human trafficking is a multifaceted and widespread problem that affects individuals across diverse demographics and intersects with other forms of oppression. This literature review delves into the prevalence of human trafficking in Albania and examines the barriers that impede efforts to prevent it, protect its victims, and prosecute its perpetrators. The review also highlights interventions that can address the underlying causes of the problem.